PEMAKNAAN KEMBALI KACA PATRI “EMPAT MUSIM DI EROPA” MUSEUM BANK MANDIRI JAKARTA - Sekarasri, Andreana Lingga (Universitas Pendidikan Ganesha, 2024)
Conservation in the Old City of Jakarta has been carried out for years, both the government and the private sector have produced many plans but its revitalization is still far from perfect. The Bank Mandiri Museum building is one of the colonial heritages which has an inscription in the form of stained glass on its main window. These glasses are not just colorful pieces, but were deliberately made to form a special story, namely the story of the Dutch's journey to find the land they were looking for, accompanied by an explanation of this stained art work (Caption) next to the main stairs. However, the caption provided is still not perfect, because the illustration on the stained glass is not fully described. Considering the lack of documentation of arts and culture in Indonesia, this needs to be paid attention to. This article is the result of a review of stained glass at the Bank Mandiri museum using a semiotic approach that is aligned with cultural studies of the colonial period. The result of this research is a new, clearer and more detailed meaning regarding the stained glass which is the object of research. Thus, it is hoped that this research can contribute to efforts to conserve the Old City as an Indonesian cultural heritage. Keywords : Stained glass, stained glass art, glass, stained, Bank Mandiri Museum. Abstrak Konservasi di Kota Tua Jakarta telah dilakukan selama bertahun-tahun, baik pemerintah maupun wasta telah menghasilkan banyak rencana namun revitalisasinya masih jauh dari sempurna. Bangunan Museum Bank Mandiri sebagai salah satu peninggalan kolonial yang memiliki “Prasasti” berbentuk kaca patri pada jendela utamanya. Kaca-kaca tersebut bukan sekadar potongan warna-warni, tetapi sengaja dibuat membentuk cerita khusus yakni cerita perjalanan Belanda menemukan tanah yang dicari disertai penjelasan mengenai karya seni patri ini (caption) di samping tangga utama. Namun caption yang diberikan masih belum sempurna, karena ilustrasi pada kaca patri tersebut tidak dideskripsikan secara utuh. Mengingat minimnya pendokumentasian seni dan budaya di Indonesia, maka hal ini perlu menjadi perhatian. Tulisan ini adalah hasil kajian ulang mengenai kaca patri di museum Bank Mandiri dengan menggunakan pendekatan semiotika yang diselaraskan dengan studi budaya tentang masa kolonial. Hasil penelitian ini adalah makna baru yang lebih jelas dan rinci mengenai kaca patri yang menjadi objek penelitian. Dengan demikian diharapkan penelitian ini dapat menjadi sumbangsih dalam upaya konservasi Kota Tua sebagai cagar budaya Indonesia.